1992
DOI: 10.1111/j.1365-2044.1992.tb02173.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrous oxide on laryngeal mask cuff pressure

Abstract: In v i m and in vivo studies A. B. LUMB AND M.W. WRIGLEY SummaryWe have studied the effect of nitrous oxide on the cufpressure o f a laryngeal mask both in vitro and in vivo. In laboratory tests. we showed that nitrous oxide and carbon dioxide diffuse across the cuff wall much more rapidly than nitrogen and oxygen. Diflkring partial pressures of these gases across the cuff wall therefore give rise to changes in volume and pressure within the cuff. We then studied 18 patients undergoing general anaesthesia with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 7 publications
0
35
1
1
Order By: Relevance
“…Lumb and Wrigley demonstrated that LMA cuff pressures can increase by as much as 50% during brief periods of N 2 O anesthesia. 75 Similarly, Trumpelmann and Cook reported on an overdistended LMA cuff after removal in a patient who had received N 2 O during anesthesia. 32 Although the cuff insufflation volume varies considerably by LMA size and type, these unanticipated increases in cuff volume during longer cases can compress the hypoglossal nerve against the hyoid bone and cause HNP symptoms.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Lumb and Wrigley demonstrated that LMA cuff pressures can increase by as much as 50% during brief periods of N 2 O anesthesia. 75 Similarly, Trumpelmann and Cook reported on an overdistended LMA cuff after removal in a patient who had received N 2 O during anesthesia. 32 Although the cuff insufflation volume varies considerably by LMA size and type, these unanticipated increases in cuff volume during longer cases can compress the hypoglossal nerve against the hyoid bone and cause HNP symptoms.…”
Section: Resultsmentioning
confidence: 94%
“…78 Similarly, Ratnaraj et al showed that maintaining ETT cuff pressure < 20 cmH 2 O in patients undergoing cervical spine surgery significantly decreased the incidence of sore throat 24 hours after extubation. 79 Intermittent pressure cuff lowering during long operations or pressure-relief valves can decrease the risk of nerve compression, 29,75,80 and it follows that LMA or ETT cuff deflation during surgical positioning could also prevent iatrogenic injury to the hypoglossal and recurrent laryngeal nerves, respectively. Bohner et al described the first use of a nerve stimulator for the successful identification and continuous monitoring of the hypoglossal nerve during an anatomically challenging carotid endarterectomy under general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of intracuff pressure in any LMA should be done with a standard of care as it reduces postoperative laryngopharyngeal adverse events [2]. Furthermore it is known that nitrous oxide can increase intracuff volume up to 50% by way of diffusion [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Among the risk factors, only the use of nitrous oxide applied to our case. It is well known that nitrous oxide will diffuse into the LMA cuff and increase the cuff pressure with time during anesthesia [14]. The cuff pressure of LMA Classic and LMA ProSeal has been shown to increase from 60 cmH 2 O to over 100 cmH 2 O following 30 min of nitrous oxide exposure [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that nitrous oxide will diffuse into the LMA cuff and increase the cuff pressure with time during anesthesia [14]. The cuff pressure of LMA Classic and LMA ProSeal has been shown to increase from 60 cmH 2 O to over 100 cmH 2 O following 30 min of nitrous oxide exposure [14]. However, there are reports that LMAs with PVC cuff are less susceptible to hyperinflation caused by nitrous oxide compared to the ones with silicone cuff [1517].…”
Section: Discussionmentioning
confidence: 99%